Management of orthodontically induced white spot lesions: a survey of the orthodontic practitioners of Pakistan - Shuja, Mirza Ezaaf; Waqar Jeelani; Maheen Ahmed; Ahsan Khalid (Journal of the Pakistan Medical Association, 2024)
Objectives: To assess the level of awareness among orthodontic practitioners about the diagnosis and management of orthodontically induced white spot lesions. Method: The cross-sectional study was conducted from August 28, 2022, to March 3, 2023, at Bakhtawar Amin Medical and Dental College, Multan, and comprised orthodontic specialists and postgraduate residents. Data was collected using a 14-item questionnaire regarding diagnosis and management of orthodontically induced white spot lesions. The questionnaire was disseminated online, and the responses were compared between the groups. Data was analysed using SPSS 24. Results: Of the 278 subjects, 205(73.7%) were residents; 156(75%) females and 49(24%) males with mean professional experience 4.24±4.08 years. There were 73(26.3%) specialists; 44(60.3%) females and 29(39.7%) males with mean professional experience 9.07±4.85 years. There were 48(66%) specialists and 131(64%) residents who thought the most commonly affected teeth with WSL were maxillary central incisors, while 30(41%) specialists and 38(33%) residents said the least commonly affected tooth was maxillary canine. Among the specialists, 29(38%) considered halting treatment and regular follow-up as the best approach to managing white spot lesions detected during orthodontic treatment, while 76(37%) residents preferred to use fluorides and casein phosphopeptide-amorphous calcium phosphate. There were significant differences between the specialists and residents for the items related to the incidence of white spot lesions, timing for additional precautions and measures for detection, management during active treatment and modalities of prevention (p<0.05). Conclusion: Despite the being fairly common in orthodontic patients, the awareness regarding white spot lesions and related management protocols was found to be dubious in orthodontic practitioners, depicting lack of a standardised protocol. Key Words: Dental caries, Dental white spots, Fixed orthodontic therapy.